Development of an Open Soft CNC System Based on STEP-NC and Function Blocks - Minhat, Mohamad; Xu, Xun (2008)
Modern manufacturing industries have put on increasing demands on computer numerical controllers (CNC) for it to be able to work with and process higher level input data described using languages such as STEP-NC, rather than the outdated G-codes. The research work described in this paper is about the development of a soft CNC controller that can process STEP-NC (ISO 14649) data. Function blocks (IEC 61499) are also used as the interface between the STEP-NC data model and the controller. The layered STEP-NC/FB architecture is proposed, which simplifies the design of the controller with layers responsible for data processing, data storage and execution. With the object-oriented, Model-View-Control design pattern, the STEP-NC/FB architecture supports the design framework, in which simulation of the machining becomes a natural and inherent part of the design process, with seamless transition from simulation to actual machining.